Evaluation of Mechanical Properties of GTAW Hardfacing Intended for the Repair of Permanent Foundry Mold Components - Koňár, R.; Mičian, M. (Archives of Foundry Engineering, 2026)
The repair of permanent steel foundry moulds is a critical industrial challenge driven by the need to minimize production costs and extend tool life. Gas Tungsten Arc Welding (GTAW) hardfacing offers a cost-effective restoration method, yet the impact of substrate dilution on the functional performance of high-alloyed layers remains insufficiently quantified. This study presents a unique evaluation of the synergy between the dilution rate and the tribological stability of the iron-based UTP-A 696 alloy deposited on an S355JR substrate. Three experimental samples with varying numbers of layers were prepared to analyze the transition from the fusion line to the pure hardfacing zone. The level of dilution was determined using spectral analysis and energy-dispersive X-ray spectroscopy (EDX). The results, supported by statistical processing, demonstrate that while the first layer suffers from significant mixing, the subsequent layers achieve a stable martensitic microstructure with a high density of complex carbides. A key finding of this research is the identification of a critical threshold for maintaining a stable coefficient of friction (0.753), providing a practical methodology for optimizing repair cycles in foundry environments. The study concludes that achieving a balance between dilution and hardness (up to 64 HRC) is paramount for the operational integrity of renovated mold components.